Hepatitis B vaccine adherence among homeless people - Vanessa Moura Carvalho de Oliveira; Marli Teresinha Gimeniz Galvão; Rômulo Veloso Nunes; Matheus Sousa Marques Carvalho; Cecília Natielly da Silva Gomes; Rosilane de Lima Brito Magalhães (Universidade Federal do Ceará, 2021)
Objective: to estimate the adherence to hepatitis B vaccine in homeless people. Methods: a cross-sectional study with 90 homeless people, with the collection of 5 ml of blood for the detection of antibody against the surface antigen of the hepatitis B virus. Results: of the total, 89 (98.9%) were vaccinated with the first dose; of these, 45 (50.7%) had antibodies against hepatitis B virus surface antigen lower than 10 IU/L; 25 (53.3%) received the second dose of hepatitis B vaccine, and nine (45.8%) participants received the third dose of vaccine. Individuals who were related to both genders were more likely to adhere to the full hepatitis B vaccine schedule. Conclusion: the low adherence to hepatitis B vaccination and the small number of participants with antibodies that confer immunity against this infection were evidenced.